ANALYSIS OF MUDHARABAH FINANCING AND MUSYARAKAH FINANCING OF ISLAMIC COMMERCIAL BANKS IN INDONESIA BEFORE AND DURING THE COVID-19 PANDEMIC - Sri Mulyati; Bambang Sugiharto; Syifa Ariella Putri; Annisa Putri Kartini (STIESA Press, 2023)
This study aims to determine the development of mudharabah financing and musyarakah of Islamic commercial banks before and during the Covid-2019 pandemic and whether there are differences in mudharabah financing and musyarakah of Islamic commercial banks in Indonesia before and during the Covid-19 pandemic. This study used samples on Islamic commercial banks registered with the Financial Services Authority with conditions before (2018-2019 period) and during the Covid-19 pandemic (2020-2021 period). The data used in the study were secondary data with data collection techniques using online data tracing and analyzed using a quantitative descriptive method that compared data on mudharabah financing and islamic commercial bank musyarakah before and during the Covid-19 pandemic on annual financial statements and tested using a test tool, namely a paired sample t-test. The results of this study can be concluded that the development of mudharabah financing and musyarakah of Islamic commercial banks before and during the Covid-2019 pandemic experienced fluctuating developments. Then there is no significant difference between mudharabah and musyarakah financing of Islamic commercial banks in Indonesia before and during the covid-19 pandemic.